2020
DOI: 10.1186/s12935-020-01552-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic characterization and innovative molecular classification of clear cell renal cell carcinoma in the Chinese population

Abstract: Background Large-scale initiatives like The Cancer Genome Atlas (TCGA) performed genomics studies on predominantly Caucasian kidney cancer. In this study, we aimed to investigate genomics of Chinese clear cell renal cell carcinoma (ccRCC). Methods We performed whole-transcriptomic sequencing on 55 tumor tissues and 11 matched normal tissues from Chinese ccRCC patients. We systematically analyzed the data from our cohort and comprehensively compared with the TCGA ccRCC cohort. Results It found that PBRM1 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The GEPIA web tool was used to determine BUB1B expression in The Cancer Genome Atlas (TCGA) (KIRC, KIRP, KICH) dataset [20]. mRNA expression profiles in the GSE40435 [21], GSE66272 [22], GSE67501 [23], GSE105261 [24], GSE126964 [25], and GSE150404 (Miekus et al, not yet published) file were downloaded from the Gene Expression Omnibus (GEO) data repository. CPTAC (Clinical Proteomic Tumor Analysis Consortium) data was downloaded from the ProTrack web tool [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GEPIA web tool was used to determine BUB1B expression in The Cancer Genome Atlas (TCGA) (KIRC, KIRP, KICH) dataset [20]. mRNA expression profiles in the GSE40435 [21], GSE66272 [22], GSE67501 [23], GSE105261 [24], GSE126964 [25], and GSE150404 (Miekus et al, not yet published) file were downloaded from the Gene Expression Omnibus (GEO) data repository. CPTAC (Clinical Proteomic Tumor Analysis Consortium) data was downloaded from the ProTrack web tool [26].…”
Section: Methodsmentioning
confidence: 99%
“…The GEPIA web tool was used to determine BUB1B expression in The Cancer Genome Atlas (TCGA) (KIRC, KIRP, KICH) dataset [20]. mRNA expression profiles in the GSE40435 [21], GSE66272 [22], GSE67501 [23], GSE105261 [24], GSE126964 [25], and GSE150404 (Miekus et al…”
Section: In Silico Analysismentioning
confidence: 99%
“…Beuselinck et al used unsupervised transcriptome analysis to identify four robust KIRC subtypes that were associated with different responses to sunitinib treatment ( Beuselinck et al, 2015 ). Zhao et al classified KIRC in the Chinese population into three classes based on gene expression, which provides practical guidelines on clinical treatment of patients with KIRC ( Zhao et al, 2020 ). However, few studies have examined the role of mast cells in KIRC and the molecular mechanisms underlying their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative mRNA stemness indices (mRNAsi) of stem cell and non-stem cell indicated that the undifferentiated samples tended to obtain lower mRNAsi within the model. Additionally, the model was externally validated in 227 stem cell samples (GSE30625) [ 22 ] and other two KIRC datasets (66 samples in GSE126964, 265 samples in GSE73731 [ 20 , 21 ]. Consistent with our previous results that undifferentiated samples scored lower mRNAsi, we distinguished stem cell from somatic cell in a strong capability with an AUC of 0.968 by mRNAsi values (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also downloaded PCBC RNA sequence data from the PCBC Synapse Portal ( https://www.synapse.org/pcbc ), consisting 16 ESC, 77 iPSC, 66 SC-derived EB, 29 SC-derived MESO, 29 SC-derived ECTO, and 36 SC-derived DE PCBC dataset [ 13 , 18 , 19 ]. Independent clear cell renal cell carcinoma validation sets (GSE73731 [ 20 ] and GSE126964 [ 21 ]) and stem cell validation set (GSE30652 [ 22 ]) with large sample size and common clinic pathological characteristics were obtained from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ).…”
Section: Methodsmentioning
confidence: 99%